PENGARUH CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA GENOTIP TANAMAN OKRA (Abelmoschus esculentus L.) - husnul khotimah (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2019)
ABSTRACT Okra (Abelmoschus esculentus L.) is one of horticulture crop that contain high nutrition. Growth and yield of this crop determined by genetic and environment factor especially water. The objective of this research was to know the effect of drought stress toward growth and yield of several okra genetypes. This research was undertaken in plastic house, Batu Kuta village Sub regency of Narmada using Split Plot design with drought stress as main plot and genotype as sub plot. Main plot consist of drought stress and without drought stress. Sub plot consist of Dompu genotype, Hybrid genotype, Red genotype and Long genotype. Every treatment combination was replicated three times. Result of this study showed that interaction between treatment and genotype of okra effected on canopy wet weight, canopy dry weight, plant height at 60 days after planting, number of leaf at 30, 60 and 90 days after planting, number of flower becoming fruit and number of good fruit. Treatment of okra genotype effected on almost all parameters except wet weight of root, dry weight of root and diameter of stem 30 days after planting. While, treatment of drought stress only effected on canopy wet weight and plant height at 60 and 90 days after planting. Long genotype had the best growth on the condition of drought. Red genotype had the best number of good fruit on the condition of drought stress and without drought stress.